2015
DOI: 10.5194/gmd-8-1085-2015
|View full text |Cite
|
Sign up to set email alerts
|

Technical challenges and solutions in representing lakes when using WRF in downscaling applications

Abstract: Abstract. The Weather Research and Forecasting (WRF)model is commonly used to make high-resolution future projections of regional climate by downscaling global climate model (GCM) outputs. Because the GCM fields are typically at a much coarser spatial resolution than the target regional downscaled fields, lakes are often poorly resolved in the driving global fields, if they are resolved at all. In such an application, using WRF's default interpolation methods can result in unrealistic lake temperatures and ice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…As a result, water temperatures from the north coast are used, which are too cold and lead to nonphysical temperature discontinuities. The adverse effect of spatially interpolating water temperatures when lakes are absent in the large-scale driving data is documented in Mallard et al (2015). (4) Warm summer bias in heavily urbanised river valleys like the Rhine river valley between the Black Forest and Taunus, the Cologne Lowlands, the Ruhr region, and also around some cities like Munich, Stuttgart, Nuremberg, Dresden, Cottbus, as well as the foreign cities of Salzburg and Strasbourg (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, water temperatures from the north coast are used, which are too cold and lead to nonphysical temperature discontinuities. The adverse effect of spatially interpolating water temperatures when lakes are absent in the large-scale driving data is documented in Mallard et al (2015). (4) Warm summer bias in heavily urbanised river valleys like the Rhine river valley between the Black Forest and Taunus, the Cologne Lowlands, the Ruhr region, and also around some cities like Munich, Stuttgart, Nuremberg, Dresden, Cottbus, as well as the foreign cities of Salzburg and Strasbourg (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…They are derived from monthly means of surface air temperature at stations of the DWD network and have a spatial resolution of 1 km (Maier and Müller-Westermeier 2010).…”
Section: Datamentioning
confidence: 99%
“…Most WRF implementations do not simulate time‐varying water body surface temperatures which affect evaporation, and hence the overlying atmospheric moisture profile. The CLM lake model, included in WRF version 3.6, requires multiyear spin‐up (Bullock et al, ; Mallard et al, , ), which is too computationally intensive for the high spatial resolutions we used. As a default, WRF initializes lakes to have surface temperatures that match nearby coastal sea surface temperature (SST), and in its absence, SST and lake temperatures are initialized with surface air temperature values.…”
Section: Methodsmentioning
confidence: 99%
“…Previous downscaling studies using much coarser horizontal resolution with fully parameterized convection revealed that using a lake model and accounting for lake depth can produce better precipitation for some regions (e.g., Small et al, ), while for others 2‐m temperatures and frozen fractions of lakes have improved at the cost of enhanced wet bias in precipitation (e.g., Mallard et al, ). Using the skin temperatures from the driver ESM may lead to erroneous lake temperatures depending on lake depth because the approach does not account for the warming and cooling time of the lakes (e.g., Mallard et al, ). Nevertheless, we are taking advantage of the much higher resolution and convection‐permitting nature of our WRF simulations and the fact that we are using monthly averaged skin temperatures from the driver data over lakes.…”
Section: Comparison Of Projected Future Changes Between Cesm and Wrf mentioning
confidence: 99%